Investigation of NiO film by sparking method under a magnetic field and NiO/ZnO heterojunction - Posak Tippo (2020)
© 2020 The Author(s). Published by IOP Publishing Ltd. Nickel oxide (NiO) film receives attention from the field of optoelectronics due to its wide band gap and high transparency. By using a sparking method, the deposition of the NiO film is facile and unique. However, the NiO film made by the sparking method indicates a porous surface with an agglomeration of its particles. In order to reduce the porousness of the NiO film, the assistance of a permanent magnet in the sparking apparatus is presented. Here, we report the investigation of the NiO film and the p-NiO/n-ZnO heterojunction deposited by the sparking method under a magnetic field. Our results demonstrate that the porosity of the NiO film was reduced by increasing the magnitude of a magnetic field from 0 mT to 375 mT. Furthermore, the crystallinity and the electrical properties of the NiO film are improved by the influent of a magnetic field. For heterojunction, the best device shows the rectification ratio of 95 and the ideality factor of 4.92. This work provides an alternative method for the deposition of the NiO film with promising applications in optoelectronic devices.